The Reliability of Anamnestic Data in the Management of Clostridium Tetani Infection in Elderly - Savioli, Gabriele; Ceresa, Iride Francesca; Giordano, Mauro; Ferrari, Ilaria; Varesi, Angelica; Floris, Valentina; Esposito, Ciro; Croesi, Barbara; Ricevuti, Giovanni; Calvi, Monica; Bressan, Maria Antonietta; Oddone, Enrico (Frontiers in Medicine, 2021)
Background: Tetanus infection remains a significant complication of wounds. Because most tetanus treatment guidelines rely on anamnestic data collected directly from patients, the congruence between anamnesis and laboratory evidence must be verified, especially in the elderly population. Aim: Assess, in both the geriatric population (>65) and the non-geriatric one, the reliability of anamnestic data for managing patients with tetanus-risk wounds, identified categories of populations most exposed to non-vaccination coverage, and assessed the agreement of the Tetanos Quick Stick (TQS) results with the therapy performed (administration of tetanus vaccine or immunoglobulin). Methods: In this retrospective single-center observational study, patients were asked their immunization status against tetanus vaccination. The decision to administer a vaccine or immunoglobulin was therefore clinical and based on anamnestic criteria. The TQS test was then given to patients who were unaware of their immunity status. Patients who thought they knew it but were not sure were given the TQS test to determine whether the anamnestic collection was supported by the test. The TQS test results were compared with the anamnestic data. Results: Most patients, geriatric and not geriatric, did not know their immune status. Among those who reported knowing their immune status, there was no agreement between the vaccine coverage declared by patients and the TQS test results (p < 0.001), mainly in geriatric patients but also in the control group. Elderly and women had significantly lower positive TQS test results (p < 0.001). There was a statistically significant discrepancy (p < 0.001) between the therapy based on anamnestic data and the TQS test results. Conclusion: The reliability of anamnestic data for the management of patients with tetanus-risk wounds is low and decreases with age, becoming minimal in geriatric patients. Elderly and women are less likely to have an effective vaccination status against tetanus.